Strategi Pembelajaran dan Dukungan Lingkungan dalam Perkembangan Anak Berkebutuhan Khusus di Sekolah Luar Biasa (SLB) Kota Bengkulu - Aisyah Bila Sapitri; Dara Siska; Suci Alima Sundari; Mendo Fikrian Anugrah (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to identify the learning strategies and environmental support applied to children with special needs at SLB N 5 Bengkulu. This research employed a descriptive qualitative approach with the subjects consisting of a teacher and a parent of a speech-impaired student selected through purposive sampling. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model. The findings reveal that the learning process implements an adaptive curriculum according to the abilities of each type of disability. Visual methods, demonstrations, and sign language are used to facilitate communication and students’ conceptual understanding. The study also found differences in communication patterns between home and school, indicating the need for consistent strategies to optimize language development. Family support and collaboration with teachers play an important role in developing students’ adaptive abilities and independence. In addition, an inclusive school environment, learning facilities, and social interactions among students contribute to the success of education for children with special needs. This study emphasizes that the effectiveness of learning in special schools is influenced by a combination of appropriate learning strategies and support from both the family and school environment. The findings may serve as a reference for developing learning strategies and educational policies for students with special needs in special education schools.